TERAPI BERMAIN ORIGAMI MENURUNKAN TINGKAT ANSIETAS ANAK USIA 3-6 TAHUN YANG SEDANG MENJALANI HOSOITALISASI - Ririn Anjarwati; Triredjeki, Hermani; Handayani, Lulut; Handayani, Sri (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2024)
Hospitalization experienced by a child is an orchestrated process or crisis requiring the child to remain in the hospital to undergo therapeutic treatment until he recovers. Feelings of anxiety are one of the impacts of the hospitalization process that children may experience when they are faced with stressors in the hospital environment and to reduce the impact of anxiety due to hospitalization on children, it is important to provide media that allows them to express their feelings of anxiety. One effective method is play therapy. Origami play therapy games are considered more effective in reducing anxiety and are suitable for ages 3-6 years. Applying nursing care to hospitalized children aged 3-6 years who experience anxiety by providing origami play therapy. The design of this scientific work uses a descriptive analysis design with a case study approach. The results of the intervention before and after providing origami play therapy showed that origami play therapy had an effect on reducing anxiety levels in hospitalized children aged 3-6 years. Origami play therapy has been proven to help reduce the level of anxiety in children who are hospitalized